Idiopathic Pleuroparenchymal Fibroelastosis Presenting in Recurrent Pneumothorax: A Case Report - Noh, Hyun Jin; Seo, Yun; Huo, Sol Mi; Kim, Tae Jung; Kim, Hyo Lim; Song, Jeong Sup (Tuberculosis and respiratory diseases, 2014)
Idiopathic pleuroparenchymal fibroelastosis (PPFE) is a rare, recently classified entity that consists of pleural and subjacent parenchymal fibrosis predominantly in the upper lungs. In an official American Thoracic Society/European Respiratory Society statement in 2013, this disease is introduced as a group of rare idiopathic interstitial pneumonias. We describe a case of a 76-year-old woman with cough and recurrent pneumothorax. She was admitted to our hospital with severe cough at first. High resolution computed tomography (HRCT) disclosed multifocal subpleural consolidations with reticular opacities in both lungs, primarily in the upper lobes, suggesting interstitial pneumonia. Rheumatoid lung was diagnosed initially through an elevated rheumatoid factor, HRCT and surgical biopsy at the right lower lobe. However, one month later, pneumothorax recurred. Surgical biopsy was performed at the right upper lobe at this time. The specimens revealed typical subpleural fibroelastosis. We report this as a first case of idiopathic PPFE in Korea after reviewing the symptoms, imaging and pathologic findings.